Calorimetric Study of N-methylacetamide in Polar and Non-Polar Solvents - Zaini, Sabeeh Jalil (Al-Nahrain Journal of Science, 2012)
We have studied the dissolution of N-methylacetamide in various solvents benzene, chloroform, acetone and water at 25°C, has been observed through the study that the Enthalpy or dissociation varies from solvent to another and this is due to the formation of hydrogen bonding between solvent (self association) or between solute and solvent molecules. The study of this kind is commensurate with the change of the solvent mixture, whether polar or non-polar.